Review paperSudden infant death syndrome, prematurity and sleeping position - Rao, Harish; Greenough, Anne (Archives of Medical Science, 2005)
Sudden infant death syndrome (SIDS), an unexpected death of an infant which remains unexplained after a thorough investigation, is the commonest cause of postneonatal mortality in the developed world. Prematurely born infants are at an increased risk of SIDS, particularly if they are slept prone. It is, therefore, important to understand why infants die of SIDS and the effects of prone sleeping position on prematurely born infants. Possible mechanisms of SIDS include failure to arouse, infection and genetic predisposition. Impaired arousal has been described during prone sleeping and in infants exposed to maternal smoking. Infection is associated with an increase in both duration and depth of quiet sleep and arousability is depressed. Infants may be at an increased risk of SIDS because of mutations leading to genetic disorders capable of causing death or having polymorphisms that might predispose to death in critical situations. The prone position has physiological advantages for prematurely born infants with and without respiratory distress in the immediate neonatal period. The few data on convalescent babies demonstrate prone posture has an advantage in improving oxygenation in infants with BPD, but is associated with less spontaneous arousals and more central apnoeas. These data emphasize that practitioners must emphasize to parents the importance of sleeping their prematurely born infants supine at the high-risk age for SIDS.